Analisis Constructed Wetlands sebagai Teknologi Pemulihan Pencemaran Air Permukaan Menggunakan Tanaman Hydrilla Verticillata dan Kangkung Air - Ayya Sophia Samad; Wilma Nurrul Adzillah; Nur Ridha Amethysia; Muhammad Gilang Bayu (Jurnal Serambi Engineering, 2024)
This research discusses the water treatment process using simple constructed wetlands. The unit or reactor is filled with sand, gravel and aquatic plants such as water spinach and hydrilla. The water used is irrigation canal water from the Citarum River in Karawang Regency. The water was fed into the reactor using a batch system and allowed to stand for 15 days. Water quality monitoring was carried out after 5, 10 and 15 days to measure the effectiveness of the water treatment. Parameters tested included temperature, pH, TDS and DHL. The results showed that the temperature in the reactor was stable. The pH increased towards normal from 6.73 on day 1 to 6.90 on day 15, although it decreased on day 5. TDS showed a removal efficiency of 23%, from 599 ppm on day 1 to 465 ppm on day 15. DHL also showed a removal efficiency of 23%, from 1200 μS/cm on day 1 to 932 μS/cm on day 15.